TETRASIKLIN RESISTANCE IN Escherichia coli ISOLATED FROM PIG FARM, PIG SLAUGTERHOUSE, AND THE ENVIRONMENT IN BANTEN PROVINCE - Pazra, Debby Fadhilah; Latif, Hadri; Basri, Chaerul; Wibawan, I Wayan Teguh (Universitas Syiah Kuala, 2023)
This study aims to determine the prevalence of tetracycline antibiotic resistance to Escherichia coli (E. coli) isolated from farms, pig slaughterhouses, and the environment in Banten Province. This study used 44 samples of solid waste/feces and effluent from pig farms, 10 samples of floor swab and effluent from pig slaughterhouses and 4 samples of the environment (river water). Isolation and identification ofE. coli using Tryptone Bile X-Glucuronide (TBX), MacConcey Agar (MCA) media and confirmed by indole test. Sensitivity test against oxytetracycline and tetracycline antibiotics was carried out using Kirby-Bauer method (disc diffusion). The results showed that oxytetracycline was the most resistant antibiotic. The prevalence of oxytetracycline resistance was highest in farms in solid waste/feces samples (56.82%), pig slaughterhouses in effluent samples (80%) and environment in river samples (upstream, downstream) (100%). Tetracycline showed the highest prevalence in solid waste/feces samples of farm (40.91%), in floor swab samples of pig slaughterhouses (70%), in upstream river samples of environment (100%). This study indicates that waste from farms and pig slaughterhouses could be a source of transmission of E. coli resistant to tetracycline antibiotics to the environment.